(untitled) (Journal of the College of Basic Education, 2026)
The research aimed to identify: the sense of responsibility among middle school students, the significance of differences in the sense of responsibility according to the stage variable (fourth, fifth), among middle school students, and to achieve the research objectives, the researchers built a scale of the sense of responsibility, consisting of (30) paragraphs, each paragraph has four alternatives, paragraphs whose psychometric properties were co firmed as the scale was applied to sample of (100 ) students who were chosen randomly in a stratified manner to extract the results of the study and the research results showed that the individuals of the research sample do not have a sense of responsibility, according to the hypothetical mean, there are no statistically significant differences in the sense of responsibility according to the stage variable (fourth, fifth) and in light of the results the researchers presented a number of recommndations and proposals.